Evaluation of various biomarkers as potential mediators of the association between Δ5 desaturase, Δ6 desaturase, and stearoyl-CoA desaturase activity and incident type 2 diabetes in the European Prospective Investigation into Cancer and Nutrition–Potsdam Study. Issue 1 (13th May 2015) - Jacobs, Simone; Schiller, Katja; Jansen, Eugène HJM; Boeing, Heiner; Schulze, Matthias B; Kröger, Janine
ABSTRACT: Background: An association between desaturase activity and risk of type 2 diabetes (T2D) has been found in epidemiologic studies, but little is known about potential mediators of this association. Objective: We aimed to investigate the potential role of diabetes-related biomarkers as mediators of the association between estimated Δ5 desaturase (D5D), Δ6 desaturase (D6D), and stearoyl-CoA desaturase (SCD) activity and T2D risk. Design: We analyzed a case-cohort study (subcohort: n = 1533; verified incident T2D cases: n = 400), nested within the European Prospective Investigation into Cancer and Nutrition–Potsdam Study involving 27, 548 middle-aged participants. We evaluated the impact of adjustment for several T2D-related biomarkers reflecting liver fat accumulation [reflected by γ-glutamyltransferase (GGT), alanine transaminase (ALT), fetuin-A, and the algorithm-based fatty liver index (FLI)], dyslipidemia (high-density lipoprotein cholesterol, triglycerides), inflammation [C-reactive protein (CRP)], and adiponectin on the association between D5D, D6D, and SCD activity, estimated with fatty acid product-to-precursor ratios derived from erythrocyte membrane proportions, and T2D risk. Results: Estimated D5D activity was inversely associated with T2D risk, whereas D6D and SCD activities were positively associated with risk of T2D [HRs (95% CIs) (highest vs. lowest tertile): 0.51 (0.36, 0.73), 1.68 (1.18, 2.39), and 1.82 (1.29, 2.58), respectively]. The association between estimated D5D, D6D, and SCD activities and risk of T2D was statistically significantly and markedly attenuated after adjustment for the FLI and, to a lesser extent, after adjustment for triglycerides, whereas adjustment for other desaturase-associated biomarkers (CRP, fetuin-A, ALT, and GGT) did not lead to appreciable attenuations. Conclusions: Liver fat accumulation, as reflected by the FLI, and dyslipidemia, as reflected by triglycerides, may partly explain the association between estimated D5D, D6D, and SCD activity and T2D risk.